2016
DOI: 10.1007/s13224-016-0867-1
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccine Requirements in Pregnant Women

Abstract: Objective To explore the importance of administering influenza vaccine during pregnancy. Materials and Methods An internet search for data, study and position papers was done. Medline and Pubmed were the frequently used search engines besides search for WHO and CDC position statements. The keywords used included, influenza vaccine, pregnancy, outcome, safety and trimesters. Results Search provided studies that had been conducted in developing nations like Bangladesh as well as developed nations like Norway and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…As an example, seasonal vaccination of pregnant women against influenza has been a recommendation of the WHO since 2005, though was not practiced widely until after the influenza pandemic of 2009. 15 During the global H1N1 pandemic, pregnant women were notably and disproportionately affected. Although pregnant women represented only 1% of the U.S. population at the time, they accounted for 5% of U.S. deaths and nearly 10% of hospitalizations related to the virus.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, seasonal vaccination of pregnant women against influenza has been a recommendation of the WHO since 2005, though was not practiced widely until after the influenza pandemic of 2009. 15 During the global H1N1 pandemic, pregnant women were notably and disproportionately affected. Although pregnant women represented only 1% of the U.S. population at the time, they accounted for 5% of U.S. deaths and nearly 10% of hospitalizations related to the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Various analyses of adverse event data found no evidence overall of an increased risk of adverse pregnancy outcomes following influenza vaccination in pregnancy [28][29][30][31][32][33]. Furthermore, influenza vaccine can be co-administered with tetanus-containing vaccines if the timings align, as recommended by the American College of Obstetricians and Gynecologists (ACOG) [34].…”
Section: Favorable Safety Profile Of Influenza Vaccination During Pregnancymentioning
confidence: 99%
“…Pregnancy is concomitant with immunological and physiological changes in many organ systems. 1 These modifications may affect the immune system's response to influenza virus infection. 2 Literature on previous influenza pandemics in 1918,1957, and 2009 has demonstrated that pregnant women were at high risk of developing complications such as pneumonia, respiratory failure, intensive care admission, sepsis, and even death.…”
Section: Introductionmentioning
confidence: 99%